(untitled) (Innovative professional education, 2025)
The article examines the use of digital technologies in history lessons as a means of enhancing the effectiveness of the educational process. The main digital tools are analyzed, including interactive maps, virtual tours, historical simulations, multimedia presentations, and online platforms for studying history. Special attention is given to the advantages of using digital technologies, such as improving the visualization of historical events, increasing students’ motivation, developing critical thinking, and fostering information literacy skills. The challenges of implementing digital technologies are also considered, particularly issues related to technical support and teachers’ methodological preparation. Keywords: digital technologies, educational process, history education, interactive methods, history visualization, digital resources.